An experimental investigation of artificial supercavitation generated by air injection behind disk-shaped cavitators - Byoung-Kwon Ahn; So-Won Jeong; Ji-Hye Kim; Siyao Shao; Jiarong Hong; Roger E.A. Arndt (International Journal of Naval Architecture and Ocean Engineering, 2017)
In this paper, we investigated physical characteristics of an artificial supercavity generated behind an axisymmetric cavitator. Experiments for the same model were carried out at two different cavitation tunnels of the Chungnam National University and the University of Minnesota, and the results were compared and verified with each other. We measured pressures inside the cavity and observed the cavity formation by using a high-speed camera. Cavitation parameters were evaluated in considering blockage effects of the tunnel, and gravitational effects on supercavity dimensions were examined. Cavity dimensions corresponding to the unbounded cavitation number were compared. In addition, we investigated how artificial supercavitation develops according to the combination of injection positions and direction.